2019
DOI: 10.3762/bjoc.15.63
|View full text |Cite
|
Sign up to set email alerts
|

Influence of per-O-sulfation upon the conformational behaviour of common furanosides

Abstract: The studies on the recently discovered pyranoside-into-furanoside rearrangement have led us to conformational investigations of furanosides upon their total sulfation. Experimental NMR data showed that in some cases drastic changes of the ring conformation occurred while sometimes only the conformation of the exocyclic C4–C5 linkage changed. Herein we describe a combined quantum chemical and NMR conformational investigation of three common monosaccharide furanosides as their propyl glycosides: α-mannose, β-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Finally, there exists a large number of studies that clearly indicate the importance of the endo ‐anomeric effect in the context of conformational preferences of furanose rings containing larger number of ring substituents . Furthermore, the compilation of the structural data performed for various glycosidic linkages involving furanose residues shows that conformational preferences induced by the exo ‐anomeric effect are also in accordance with our predictions.…”
Section: Resultssupporting
confidence: 87%
“…Finally, there exists a large number of studies that clearly indicate the importance of the endo ‐anomeric effect in the context of conformational preferences of furanose rings containing larger number of ring substituents . Furthermore, the compilation of the structural data performed for various glycosidic linkages involving furanose residues shows that conformational preferences induced by the exo ‐anomeric effect are also in accordance with our predictions.…”
Section: Resultssupporting
confidence: 87%
“…In our previous studies of the conformational changes in furanoside rings upon their complete sulfation, we revealed the main conformers of the non-sulfated galactofuranoside. These results were supported by evidence from NMR spectroscopy, such as intra-ring H-H coupling constants and NOE (Gerbst et al, 2019a). The main determined conformers for the nonsulfated rings were C3-exo or the ones similar to them according to Cremer-Pople parameters (Figure 1).…”
Section: Introductionsupporting
confidence: 60%
“…The objects of the study are shown in Figure 2 . Disaccharides 1 and 2 (that relate to the fragments of Cryptococcus neoformans galactoxylomannan) are model structures lacking an amino group in the propyl aglycon; synthesis of the full structures is described in the study by ( Dorokhova et al, 2021 ), monosaccharide 3 is from the study by ( Gerbst et al, 2019a ), and synthesis of 3-O-(R)-lactic acid derivative 4 (that relates to the fragment of Enterococcus faecalis diheteroglycan) and its (S)-isomer 5 is described in the study by ( Krylov et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the sulfation effect on metal binding preference results from a combination of inter‐ and intra‐molecular interactions, electrostatic attraction or repulsion and conformational differences. The effect of sulfation on the conformation of furanosides and GAG was previously reported . It shows that sulfation alters the conformation of saccharides already on the monosaccharide level.…”
Section: Resultsmentioning
confidence: 63%
“…The effect of sulfation on the conformation of furanosides and GAG was previously reported. [68,69] It shows that sulfation alters the conformation of saccharides already on the monosaccharide level. It is reasonable to concludet hat sulfation will induce significant conformational changes also on the oligo-and poly-saccharide level that can result in modulation of the affinity toward metal ions.…”
Section: Xps Analysis Of Msha4 After Exposure To Heavy Metal Ionsmentioning
confidence: 99%